MANAGEMENT OF INSOMNIA USING PHARMOCOLOGY OR NON- PHARMACOLOGY - Ghaddafi, Muammar (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 In s o m n i a i s a s y m p t o m ra t her t han a d i agno s i s t hat m a y l ead t o i rr it ab i li t y , d i ss a ti s fac ti on and decrea s e i nd i v i dual produc ti v it y . I n s o m n i a can be d i v i ded i n t o pr im a r y and s econda r y s y m p t o m w h i ch cau s e b y o t her cond iti on, but t he m e chan i s m on h o w t h i s happened s ti ll unc l ear. In add iti on, re l a ti on be t w een i n s o m n i a and o t her c li n i cal prob l e m i s a l wa y s undef i ned becau s e i t i s i m po ss i b l e t o f i nd out t he re l a ti on be t w een cau s es and con s equences of t h i s s y m p t o m . Prac titi o n er can choo s e e it her phar m a co t hera p y or non-phar m ac o t hera p y i n m a n age m e n t of i n s o m n i a pa ti en t . S i de effec t s and eff i ca c y of phar m aco t h era p y m u s t be con s i dered before w e pr e s cr i be a m ed i c i ne t o de pa ti en t . We a l s o can Choose non-pha r m aco t h era p y w h i ch i s w it hout s i de effec t s , but can be s a m e effec ti ve as phar m ac o t hera p y and even m ore.
Keywords: Insomnia, managemen